Over Two Years of Sustained Remission With Olaparib Monotherapy in Stage IV Non‐Small Cell Lung Cancer With ATM Mutation: A Case Report - Zhiting Tang; Ran Bi; Mutasim Idriss; Qian Wang; Qi Wang; Makiko Ban‐Hoefen (Cancer Reports)
ABSTRACT Background Ataxia telangiectasia mutated (ATM) mutations represent the most common homologous recombination deficiency (HRD) mutation in non‐small cell lung cancer (NSCLC). However, their therapeutic role in NSCLC has not been established. Case Here, we present a case of a 91‐year‐old male with metastatic NSCLC who progressed on multiple lines of treatment. Next‐generation sequencing revealed ATM mutations, leading to the initiation of olaparib, which successfully achieved remission over a two‐year period. Conclusion This case underscores the promising role of olaparib in treating NSCLC with HRD, particularly ATM mutations, highlighting the importance of molecular testing and targeted therapies.